US Office of Naval Research Arctic Research Laboratory, Point Barrow, Alaska - Britton, M. E. (Polar Record, 1967)
The Arctic Research Laboratory (ARL) is a year-round, continuing, basic research facility, funded by the Office of Naval Research (ONR), US Department of Navy, and located in lat 71° 21'N, long 156° 46'W, near Point Barrow, on the Arctic coast of Alaska. It was established in 1947 not, as could be reasonably expected, only to further investigations of immediate and practical use to the Navy, but also to support work of purely general scientific interest. Scientists from other countries were also invited to make use of its facilities. ARL represents a laudable co-operation between government support and private scientific enterprise.